Comparison of High-Performance Liquid Chromatography and Capillary Electrophoresis in the Screening of Haemoglobinopathies - Asghar, Shumaila; Mahmood Abbasi, Asad; Zafar, Jawad; Mahmood, Rafia; Zahir, Saima; Khan, Maria (Pakistan Armed Forces Medical Journal, 2024)
Objective: To compare the results of High-Performance Liquid Chromatography and Capillary Electrophoresis in the screening of haemoglobinopathies.Study Design: Cross-sectional study.Place and Duration of Study: Department of Haematology, Armed Forces Institute of Pathology, Rawalpindi Pakistan, from May 2020 to Nov 2020.Methodology: Ninety(90) newly diagnosed patients with haemoglobinopathies were included. Patients with a history of recent blood transfusion (